Scaphochlamys disticha (Zingiberaceae), a new species with distichous inflorescence from Peninsular Malaysia - Sam, Yen Yen; Ibrahim, Halijah (Pensoft Publishers, 2018)
A new species of ginger, Scaphochlamys disticha Y.Y. Sam & H. Ibrahim, sp. nov., from Terengganu, Peninsular Malaysia is described and illustrated; colour plates and conservation status are also provided. The species is characterised by its large inflorescence with distichously arranged floral bracts.